Identifying Students’ Religiosity and Character Strengths in a Multiculturalism Life Consequence - Tukiyo Tukiyo; Didik Rinan Sumekto; Yulinda Erma Suryani (AL-ISHLAH: Jurnal Pendidikan, 2023)
The multiculturalism values which exist among students promote their character, religiosity and character strength in their personal life.  This study aims to investigate the religiosity and character strength among associates and students’ with diversity, undergraduate degrees at a private university in Klaten, Central Java. The     instruments address students’    religiosity and character strengths, endorsing male (114 or 30.4%) and female (261 or 69.6%) students who lived in and outside the Klaten district. 313 or 83.5% of respondents were residing in Klaten district,  whereas the remainder of, 62  or  16.5%, were originally inhabited from outside Klaten. This study used a quantitative descriptive with 375 respondents. Data were collected from a Google form to facilitate respondents’ accessibility in filling out the questionnaire and analyzed by using multivariate assumption tests of normality, homogeneity, and covariance variance matrix. The results proved that the value of religiosity (F = 1.641; p = .000) and character strength (F = 1.683; p = .000) from the Levene’s test, whilst the homogeneity test of covariance showed 7.104; F = .771; p =.643. Students’ religiosity ranked in the medium category (67.2%) as well as students’ character strength  (66.4%).   These meant no significant differences in religiosity and character strength among gender-based students’ domiciles.